Exploring An Approach Towards Measuring Student Learning Outcomes: A Case Study For A Pre-Service Teacher Education Programme at A University In Vietnam - Thi Giao Chi Le (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2023)
Higher education in South-East Asia as elsewhere in the world has been under transformations as it aims to meet increasing demands for quality workforce to fuel the economic growth and global integration. Higher education institutions are striving for quality of student learning and measures have been taken, be they quality assurance initiatives or responsible educational practices, to ultimately demonstrate their accountability towards their educational outputs – the achievement of their student learning outcomes. This paper presents an approach to measuring the attainment of student learning outcomes for a pre-service teacher education programme at a university in Vietnam. It shows attempts being made to an assessment plan to determine whether the intended learning outcomes have been achieved and to what extent. The process involves establishing a set of performance indicators (PIs) which well correspond to the set learning outcomes and identifying various types of direct student achievement data being collected and benchmarked against the set targets The findings allow some generalisations to be drawn on the overall performance of student learning with certain aspects being reported to outperform their counterparts in the programme, especially in the outcomes towards lifelong learning, personal and professional development. The paper also suggests the use of indirect evidence collected via surveys to stakeholders to allow a more comprehensive picture of the performance of student learning from which better-informed decisions could be made on changes in curricular design and delivery.